'Why do I think what I think I am?': Mothers' and fathers' contributions to adolescents' self-representations. Issue 8 (17th November 2021) - Silva, Carla Sofia; Martins, Ana Catarina; Calheiros, Maria Manuela
ABSTRACT: This study analyzed adolescents' self-representations construction process, relying on the Looking Glass Self Hypothesis (LGSH), within parent-child relationships – that is,  the mediating role of mothers' and fathers' reflected appraisals (i.e., adolescents' perceptions of their parents' appraisals of them) in associations between parents' actual appraisals and adolescents' self-representations. Participants were 221 adolescents, 12-16 years old, and both their parents. The standard paradigm was used to measure the LGSH elements: self-representations were measured with the Self-Representation Questionnaire for Adolescents, which was reworded to measure parents' actual and reflected appraisals. Structural equation modeling with bootstrap estimation supported the LGSH for all self-representation domains under analysis. Results are discussed considering the specificities of the adolescent-mother and adolescent-father relationships, and the different self-representation domains analized.